2007
DOI: 10.1097/01.hp.0000275298.69543.5c
|View full text |Cite
|
Sign up to set email alerts
|

Correction Factors for More Accurate Estimates of Exposure Rates Near Radioactive Patients: Experimental, Point, and Line Source Models

Abstract: Radioactive patients may expose others after radiopharmaceutical administrations, and evaluation of the absorbed dose or exposure rates close to patients is important in keeping radiation doses as low as reasonably achievable. Two theoretical exposure models, point source and line source models, are frequently used to calculate exposure or dose rates without the support of actual measurements. If measurements of exposure rates were performed near patients, an experimental exposure model could be implemented. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
2
10
1
Order By: Relevance
“…The result revealed that the scattered radiation from the concrete walls, floor, and ceiling of the room contributed 27.5% of the total dose rate at a distance of 1 m from the 131 I patient in the room, thus to a large extent explaining the systematic underestimation of the line source predictions. This roomscattering contribution was greater than that reported by Willegaignon et al (2007) because the measurements were performed near a corner of the room. The results of this study also indicated that the contribution of room scattering can be reduced to only approximately 3.8% if all the inner surfaces of the room are covered with a sheet of lead.…”
Section: Effective Range Of the Line Source Modelcontrasting
confidence: 53%
See 3 more Smart Citations
“…The result revealed that the scattered radiation from the concrete walls, floor, and ceiling of the room contributed 27.5% of the total dose rate at a distance of 1 m from the 131 I patient in the room, thus to a large extent explaining the systematic underestimation of the line source predictions. This roomscattering contribution was greater than that reported by Willegaignon et al (2007) because the measurements were performed near a corner of the room. The results of this study also indicated that the contribution of room scattering can be reduced to only approximately 3.8% if all the inner surfaces of the room are covered with a sheet of lead.…”
Section: Effective Range Of the Line Source Modelcontrasting
confidence: 53%
“…De Carvalho et al (2011) presented a comparison of point, line, and phantom dose rate estimates around radioactive patients. For three therapy types, the point source model overestimated the phantom dose rate source model at ratios of 1.45-2.10 at 1 m, and the line source model exhibited improvements and overestimated by approximately 20-70% the dose rates at 1 m. According to Willegaignon et al (2007) and Yi et al (2013), irrespective of the source model used, the calculated dose rates typically exceeded the measured results. They have suggested "correction factors" or "self-shielding factors" for correcting the overestimation and increasing the dose estimates' accuracy.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…As expected, this is less than the conservative theoretical exposure rate constant for an unshielded point source of 223 Ra in equilibrium with progeny of approximately 0.05 μSv h −1 MBq −1 (Smith and Stabin 2012). The measurement of dose rates in this low range can be affected by statistical variability, background fluctuations (especially in an active nuclear medicine department), and geometry (Willegaignon et al 2007; de Carvalho et al 2011). For example, in one patient, the normalized exposure rate at 1 m was measured as 0.1 μSv h −1 injected MBq −1 immediately following administration, a value that was likely artificially high due to background fluctuations in the nuclear medicine injection area during the measurement.…”
Section: Discussionmentioning
confidence: 99%